Effects of Seasonal variation on Growth Performance of Mirror carp (Cyprinus carpio Ver. specularis) in Earthen Nursery Ponds - Hossain, Md. Istiaque; Khatun, Murshida; Kamal, B.M. Mostafa; Habib, Kazi Ahsan; Tumpa, Ananna Sen; Subba, Bharat Raj; Hossain, Md. Yeamin (Our Nature, 2015)
The experiment was conducted to determine the effect of seasonal variation on growth performance of Cyprinus carpio fry in six earthen ponds during December 2011 to June 2012 covering winter (WS) and summer season (SS). Stocking density was 6250 per decimal with a mean weight of 0.192±0.002 (g). This study was done with three replications for each season. During the WS, the mean values of water parameters were temperature 16.78±2.17, transparency 32.67±1.9 cm, dissolved oxygen 5.88±2.18 mg/l, pH 8.24±0.49, total alkalinity 184.72±22.72, and ammonia nitrogen 0.21±0.05 whereas the mean value of water parameters in SS were temperature 30.56±1.51, transparency 30.61±1.71cm, dissolved oxygen 4.3±1.37 mg/l, pH 8.33±0.24, total alkalinity 274.95±6.73 mg/l, and ammonia nitrogen 0.16±0.05 mg/l. Mean values of survival and specific growth rates were 58.94±0.95 and 2.45±0.03 in WS and 67.85±4.27 and 4.00±1.03, in SS respectively. Mean gross and net productions in WS were 1581.94±71.55 kg ha-1 60 d-1 and 1285.03±69.84 kg ha-1 60 d-1 and, 4262.74±147.81 kg ha-1 60 d-1 and 3964.74±145.74 kg ha-1 60 d-1, in SS respectively. Therefore, it can be concluded that mirror carp fry production was better in SS than in WS. DOI: http://dx.doi.org/10.3126/on.v12i1.12252 Our Nature (2014), 12(1): 8-18